(untitled) (Research, Society and Development, 2018)
This essay proposes a synthetic picture of digital professional and academic magazines published in Italy about Latin America through a bibliographic study and also by the use of secondary sources as websites, books and magazines. The analysis shows that there are eighteen magazines, mainly open access (77.7%), which are primarily dedicated to humanities and social sciences, including history but also current affairs. Instead there are just four magazines subject to payment (22.3%).